Crack analysis for some structures subjected to thermal and dynamic loads - Nhu, Ngo Huong (Vietnam Journal of Mechanics, 2008)
Numerical methods of crack analysis for some 2D-elasticity problems with thermal and dynamic loads are considered in this work. The general steps of the algorithm are presented. Some programs are written by Gibian languages in the codes Castem for crack analysis of different structures. Numerical illustrations are realized for the crack dam model, the plate with one and two cracks the plate with crack at the hole subjected to under variable tension of thermal loads. The influence of the temperature, dynamic loads or position of the crack on fracture parameters for these structures are investigated. The given programs may be useful for estimating the failure of dams, tunnels or other structures